Nanomaterials and Nanochemistry - Bréchignac, C.; Houdy, P.; Lahmani, M. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Nanomaterials are a fast developing field of research and applications lie in many separate domains, such as in hi-tech (optics, electronics, biology, aeronautics), but also in consumer industries (automotive, concrete, surface treatments (including paints), cosmetics, etc.).